Peran Pembelajaran Visual dengan Materi Sistem Respirasi pada Kelas X SMP - Telaumbanua, Jun Mardin; Gea, Yusmori Isra Putraman; Lase, Natalia Kristiani (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine the effectiveness of visual learning method strategies for efficiency in the learning process of students in class X. The method used is literature study. This research is a type of research that collects data from literature. Data collection techniques through reference books, journals and websites. The initial step of this research is to first study the results of research regarding the role of visual learning in learning at school. Data collection through books, journals and websites. Data analysis was carried out using the stages of data reduction, data presentation, and drawing conclusions. The results of the research show that the use of visual media in biology learning with material on the respiratory system in class can help students understand and remember, with contributions from the teacher in explaining further about the respiratory system in learning. Thus, the learning process using visual media can help students learn and become a more effective and interactive learning strategy in improving student learning outcomes